# Math

posted by .

how do you solve this by substitution:
step by step

1. 5x-y=16
5x+2y=13

2. 3x-3y=9
2x-4y=-16

3. x=-6y
y=2/3x+5

thank you!

• Math -

Please only post your questions once. Repeating posts will not get a quicker response. In addition, it wastes our time looking over reposts that have already been answered in another post. Thank you.

See your later post.

## Similar Questions

1. ### math/algebra

solve each of the following systems by substitution. 16) 5x -2y = -5 y - 5x = 3 20) 8x -4y = 16 y = 2x - 4 28) 4x -12y = 5 -x + 3y = -1 Step one: Solve on of the equations for one of the variables. y=2x-4 Step two:Substitute the expression …
2. ### Algebra help

f(x)=x^3-4x^2-x+4 How do I find the x-intercept for this?
3. ### Math need by 9pm cst

Solve by substitution method. Show step by step process. 4x+5y=27 x=26-4y
4. ### algebra

Solve by substitution method 3x+8y=17 2x+y=14 please show step by step so i can understand better. I keep getting it wrong at the end.
5. ### algebra!

how do you solve this by substitution: step by step 1. 5x-y=16 5x+2y=13 2. 3x-3y=9 2x-4y=-16 3. x=-6y y=2/3x+5 thank you!
6. ### pre algebra

solve the equation step by step.list each step along with the property you used during that step. -5 x 1 x 11 x 4
7. ### algerbra

solve the equation step by step list each step along with the property you used during that step -5*1*11*4
8. ### Algebra 1--Step-by-Step

Can someone show me how to solve these step-by-step?
9. ### Math

In which step is the error? Step 1: Let x = 1 and y = 1. Step 2: By substitution xy = y^2. Step 3: Multiplying both sides by -1, -xy= -y^2. Step 4: Adding x^2 to both sides, x^2-xy=x^2-y^2. Step 5: Factoring, x(x-y)=(x+y)(x-y). Step
10. ### Pre-Calculus

Solve the system by the substitution method. Show your work. 2y - x = 5 x2 + y2 - 25 = 0 I solved the problem but I got it wrong for some reason..can you solve it step by step?

More Similar Questions